Changes over Time in Intracranial Air in Patients with Cerebral Air Embolism: Radiological Study in Two Cases. (12th November 2015) - Kaichi, Yoko; Kakeda, Shingo; Korogi, Yukunori; Nezu, Tomohisa; Aoki, Shiro; Matsumoto, Masayasu; Iida, Makoto; Awai, Kazuo
Abstract : Cerebral air embolism can be easily identified on computed tomography (CT) scans. However, changes in the distribution and amount of intracranial air are not well known. We report two patients with cerebral air embolism and present imaging findings on the serial changes in the intracranial air. We thought that the embolic source was venous in one patient because CT showed air inflow in cortical veins in the bilateral frontal areas, reflecting air buoyancy. In the other patient, CT showed air inflow into not only the cortical veins but also the bilateral cerebral hemispheres and we thought this to be a paradoxical cerebral air embolism. We found that intracranial air can be promptly absorbed and while cerebral infarcts due to air are clearly visualized on diffusion-weighted images (DWI), the air may rapidly disappear from images. In patients with suspected cerebral air embolism whose CT findings show no intracranial air, DWI should be performed because it may reveal cerebral infarction due to cerebral air embolism.